Needs and possibilities for improving maternal nutrition in rural Tanzania - Temu, Alice Gibron; Justus Liebig University Giessen (My University, 2009)
Maternal mortality remains high particularly in developing countries where 99% of the deaths occur. Each year more than half a million women die from treatable or preventable complications during childbirth. Little progress has been made in saving women s lives between 1990 and 2005. Globally, maternal mortality has decreased by less than one per cent per year during this period. Although other regions such as Northern Africa, Latin America and the Caribbean as well as South-Eastern Asia managed to reduce their maternal mortality ratio by one-third, in Sub-Saharan Africa, the region with the highest level of maternal mortality, progress made was negligible. This study investigated nutrition and health problems that were faced by women of childbearing age in the Iringa rural areas in Tanzania. Furthermore, it outlined special needs and possible interventions that are feasible, sustainable, and implementable to improve maternal health and nutrition. The following specific objectives were studied: Factors associated with the nutritional status among women of reproductive age in the Iringa Rural District in Tanzania. Food availability, food consumption, and nutrient intake of the women. Women s knowledge, awareness, and perception towards the importance of micronutrients in pregnant women and the outcomes. Availability, accessibility, and utilization of health care services among women in the study area.Sampling included women aged between 15 and 44 years living in Malinzanga village. The sample size (389) calculation was based on the country s prevalence of anemia in women of reproductive age. The study was a cross sectional community baseline survey. Data were collected in one continuous phase between February and April 2008. Data collection included food frequency questionnaire, a 24-hour dietary recall, focus group discussions, participatory observation, Bitot s spots- and goiter examinations, height, weight, mid-upper arm circumference (MUAC), plasma levels for hemoglobin concentration (Hb), soluble transferrin receptor (sTfR), retinol-binding protein (RBP), C-reactive protein (CRP) and acid glycoprotein (AGP). Microsoft Excel (MS Office 2007), Statistical Package for the Social Sciences (SPSS version 17.0), and Analysis of Moment Structures (Amos 16.0) were used for data analysis. Not only did the women of Malinzanga village have energy malnutrition but they also suffered from micronutrient deficiencies as well as illnesses which made them more vulnerable. The nutritional status of the women differed with age, location, tribe, main source of income, and assets. Factors associated with the nutritional status of women in the study area were complex and influenced each other. Food insecurity negatively affected women s micronutrients status: it increased the risk of vitamin A and iron deficiency, as well as malaria and diarrhea illnesses. A prevalence of 26% anemia and 55% vitamin A deficiency was observed. Moreover, the nutrition influenced the women s vitamin A and iron status, and these statuses influenced each other. Most of the women in the study sample had never heard of iron, vitamin A, and iodine and did not know good food sources for these nutrients or their importance to maternal health. Consequently, their dietary intake as well as micronutrient status, and hence their health status, was negatively affected.Antenatal care services seeking behavior in the study area was relatively low. The long distance to the dispensary was a common reason for not attending the antenatal care clinics during pregnancy. In addition, poor economy and poor health and nutrition education were among the factors affecting the attendance of women at antenatal care services.The findings of the current study indicate that there is an urgent need to improve maternal nutrition in the rural areas of Tanzania. Therefore, the following measures are recommended: 1. Revision of the Tanzanian Nutrition Policy: Free iron and vitamin A supplements should be distributed based on WHO recommendations, especially in remote areas. 2. Improvement of community nutrition education both quantitatively and qualitatively: The topics of causes and consequences of malnutrition, methods of prevention, and the benefits of good nutrition to maternal and child health should be covered. 3. Improvement of malaria control and diarrhea prevention, training of the health care providers, as well as increasing salaries to motivate the health care providers to remain and provide quality care in the rural areas, especially in remote areas such as Malinzanga village.4. Fortification of vitamin A in maize flour and vegetable oil: these products are commonly used, easily available, and accessible to all people in Tanzania at all times, even in remote areas. Problem: these products are often not centrally produced but people in the rural areas often produce them locally.5. Revision of the fee-for-service policy of health care institutions to improve access by poor citizens. 6. Assessment of the impact of improved diagnostic-methods for examination of the health status of the women.7. Use the case of Malinzanga village and a pilot study on implementation processes. Multi-disciplinary sectors should work together in planning and implementing improved health and nutrition services and activities in the rural areas of Tanzania. This will not only improve the overall nutrition status of the most affected women in the remote areas, but also help the country in the process of achieving the first, fourth, fifth, and sixth Millennium Development Goals. Its effect will directly reduce child mortality, improve maternal health, and indirectly contribute to combating HIV/AIDS, malaria, and other diseases.

Die Müttersterblichkeit ist immer noch hoch, besonders in Entwicklungsländern, wo 99% der Todesfälle vorkommen. Jedes Jahr sterben eine halbe Million Frauen von behandelbaren oder vermeidbaren Komplikationen bei der Entbindung. Zwischen 1990 und 2005 wurden wenige Fortschritte erzielt, um die Leben der Frauen zu retten. Weltweit ist die Müttersterblichkeit in diesem Zeitraum nur um weniger als ein Prozent pro Jahr gesunken. Obwohl andere Regionen wie Nordafrika, Lateinamerika, die Karibik und Süd-Ost-Asien ihre Müttersterblichkeit um ein Drittel reduzieren konnten, ist in Subsahara-Afrika, welches mit der höchsten Rate belastet ist, kaum ein Rückgang zu verzeichnen. Die vorliegende Studie untersuchte die Ernährungs- und Gesundheitsprobleme von Frauen im gebärfähigen Alter in ländlichen Gebieten in Iringa, Tansania. Des Weiteren zeichnet die Studie spezielle Anforderungen und mögliche Interventionen auf die mütterliche Gesundheit und Ernährung zu verbessern, die gleichzeitig plausible, nachhaltig und implementierbar sind. Die Studie beinhaltete folgende Untersuchungsschwerpunkte: Faktoren, die mit dem Ernährungsstatus der Frauen im reproduktiven Alter im Iringa Rural Distrikt, Tansania zusammenhängen. Verfügbarkeit von Lebensmitteln sowie Nahrungs- und Nährstoffaufnahme der Frauen. Wissen der Frauen, ihr Bewusstsein und ihre Wahrnehmung gegenüber der Bedeutung von Mikronährstoffen für Schwangere und Kinder. Verfügbarkeit, Zugang und Nutzung von Gesundheitseinrichtungen von Frauen in der untersuchten Region. Die Studienauswahl beinhaltete Frauen des Dorfes Malinzanga im Altern zwischen 15 und 44 Jahren. Stratifizierung und eine einfach randomisierte Auswahlmethode wurden für die Kalkulation der Stichprobengröße angewendet. Die Berechnung der Stichprobengröße (389) beruhte auf der Prävalenz anämischer Frauen im reproduktiven Alter Tansanias. Die Studie war eine Baseline-Querschnittsstudie auf Gemeindeebene. Die Datenerfassung Verzehrhäufigkeits-fragebogen, 24-Stunden-Ernährungsprotokoll, Experteninterviews und Fokus-gruppendiskussionen), partizipative Beobachtungen, Untersuchung auf Bitot sche Flecken und Goiter, Messung von Größe, Gewicht, mittlerer Oberarmdurchmesser (MUAC), Plasmalevel für Hämoglobin (Hb), soluble Transferrin-Rezeptor (sTfR), retinolbindendes Protein (RBP), C-reaktive Protein und Acid Glycoprotein (AGP). Daten wurden analysiert mit Hilfe von Microsoft Excel (MS Office 2007), Statistical Package for the Social Sciences (SPSS Version 17.0) und Analysis of Moment Structures (Amos 16.0). Die Frauen im Dorf Malinzanga litten nicht nur unter Energie-Malnutrition, sondern auch unter Mikronährstoffmangel, Krankheiten und Infektionen, welches wiederum ihr Risiko für Krankheiten und Infektionen erhöht. Der Ernährungsstatus der Frauen unterschied sich mit dem Alter, Wohnort, Volksstamm, Haupteinkommensquelle und Eigentum. Die mit dem Ernährungsstatus der Frauen in der untersuchten Region assoziierten Faktoren waren komplex und beeinflussten sich gegenseitig. Lebensmittelunsicherheit beeinträchtigte negativ ihren Mikronährstoffstatus: es steigerte die Anfälligkeit für Vitamin A- und Eisenmangel, aber auch für Malaria und Durchfall. Die Mehrzahl der Frauen in der Studienpopulation hatte vorher noch nie von Eisen, Vitamin A und Jod gehört, sowie von Lebensmitteln, die diese Nährstoffe enthielten. Des Weiteren konnten sie nicht die Bedeutung dieser Nährstoffe für die mütterliche Gesundheit benennen. Demzufolge waren ihre Nahrungsaufnahme, ihr Mikronährstoffstatus und so ihr Gesundheitsstatus negativ beeinträchtigt. Das Aufsuchen von Schwangerschaftsfürsorgeeinrichtungen von Müttern in der untersuchten Region war relativ gering. Einer der Hauptgründe für dieses Verhalten war laut der Frauen die lange Distanz zur Gesundheitsstation. Außerdem wurde das Aufsuchen von Schwangerschaftsfürsorge durch eine schlechte Wirtschaftslage, geringe Gesundheits- und Ernährungsbildung beeinflusst. Die Ergebnisse dieser Studie zeigen, dass eine Notwendigkeit besteht, den mütterlichen Ernährungsstatus in ländlichen Populationen in Tansania zu verbessern. Folgende Maßnahmen werden empfohlen: 1. Überarbeitung der tansanischen Ernährungspolitik: Eisen und Vitamin A Supplemente sollten kostenlos, basierend auf WHO Richtlinien, verteilt werden, via. in schwer erreichbaren Regionen. 2. Verbesserung der allgemeinen Ernährungsbildung; qualitativ als auch quantitativ über: Ursachen und Konsequenzen der Malnutrition, Methoden der Prävention. 3. Verbesserung der Malaria-Kontrolle und Durchfallprävention, der Bildung von Gesundheitsfürsorge-Anbieter, aber auch der Vergütung dieser für die Motivation weiterhin in ländlichen Regionen ihre Dienste anzubieten, besonders in schwer erreichbaren Gebieten wie z.B. Malinzanga. 4. Fortifizierung von Maismehl und Pflanzenöl mit Vitamin A: Diese Produkte werden weitläufig genutzt, sind reichlich vorhanden und sind für die ganze tansanische Bevölkerung zugänglich, sogar in schwer erreichbaren Gebieten. Problem: Diese Produkten sind nicht zentral verarbeitet, sondern im lokal Gemeinde.5. Beurteilung der Verantwortlichkeit für eine Gesundheitsfürsorgeservicegebühr um die Gesundheit der armste Leute zu verbessern.6. Beurteilung der Auswirkung von Diagnosemethoden auf den Gesundheitsstatus von Frauen. 7. Anwendung der Fallbeschreibung des Dorfes Malinzanga und einer Pilotstudie für Implementierungsprozesse. Eine Zusammenarbeit von multidisziplinären Sektoren im Bereich der Planung und Implementierung von verbesserten Gesundheits- und Ernährungsservices sowie Aktionen in ländlichen Gebieten Tansanias ist von Nöten. Dies würde nicht nur die Ernährungssituation der am meisten betroffenen Frauen aus ländlichen Regionen und schwer erreichbaren Gebieten verbessern, sondern auch Tansania bei dem Prozess helfen, das erste, vierte, fünfte und sechste Millennium Development Goal zu erreichen. Dadurch kann direkt die Kindersterblichkeit reduziert sowie die mütterliche Gesundheit verbessert werden. Außerdem werden so indirekt HIV/AIDS, Malaria aber auch andere Krankheiten bekämpft.
Bedarf und Möglichkeiten der Verbesserung der Ernährung von Frauen im gebärfähigen Alter im ländlichen Tansania
Keywords: Ernaehrung; Frauenernaehrung; Mikronaehrstoffemangel; Vitamin A-Mangel; Eisen-Mangel; Nutrition; Maternal nutrition; Micronutrient deficiencies; Vitamin A deficiency; Iron deficiency; ddc:360